MicroRNA-21 Expression in Prostate Cancer: A Systematic Review - Maria Ulfa; Krisna Murti; Irsan Saleh; Debby Handayati (Indonesian Journal of Global Health Research, 2025)
Prostate cancer is the second most prevalent and fourth largest cause of death for men globally. Meanwhile, in Indonesia, prostate cancer ranks and is the fourth leading cause of death. Molecular studies continue to be conducted to understand the molecular heterogeneity, both genetic and epigenetic, that affects the progression of prostate cancer, one of which is the role of microRNA. This study aims to analyze the expression profile of microRNA-21 associated with the development and aggressiveness of prostate cancer. Comprehensive search into three databases; PubMed, Cochrane Library, and Science Direct was performed by authors. The study that best met the inclusion criteria was chosen from among duplicates. The QUADAS-2 (Quality Assessment of Diagnostic Accuracy Studies) tool was used to assess the risk of bias before the relevant data were retrieved for analysis. There were eleven studies that included a variety of sample sources, sample size and methods. Although a number of the studies had unclear standard reporting, the research overall quality was acceptable. For the results, Prostate cancer samples showed a significantly higher expression level of miR-21 than controls in ten of the studies, and was linked to cancer aggressiveness. In one study, the expression of miR-21 did not significantly increase, despite the use of extracellular vesicle isolation samples.